DRONE TECHNOLOGY IN EDUCATION: A BIBLIOMETRIC ANALYSIS - Farha Mohamed Yasin; Fatin Aliah Phang Abdullah; Nazri Nasir; Jaysuman Pusppanathan (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Drone technology has shown a great deal of potential in transforming teaching and learning. In order to investigate the intellectual landscape around the integration of drone technology in education, this study undertakes a thorough bibliometric analysis. Various scholarly repositories were examined in detail to compile relevant papers. In the field of drone technology in education, this research presents a comprehensive bibliometric analysis, examining 1,147 papers indexed in Scopus. By utilizing VOSviewer for data visualization and analysis, the research identifies key trends, influential publications and collaborative patterns in the field. The data reveals an increasing interest in using drones in a variety of educational contexts with a focus on environmental studies, STEM education and experiential learning. Moreover, the study highlights significant contributions from interdisciplinary partnerships and specialized research groups, emphasizing the interdisciplinary character of integrating drone technology into educational practices. In summary, this bibliometric investigation offers valuable insights into the present status and future trajectories of research on harnessing drone technology to enhance educational methodologies. The outcomes of this study offer valuable guidance for researchers, educators, and policymakers seeking to integrate drones into curricula, equipping students with essential skills and competencies for future careers.